(untitled) (Global Journal of Human-Social Science, 2024)
The objective of this article is to explore ethical issues surrounding Venezuelan migrant students in Peru s education system by examining stereotypes against them evaluating the system s impact on their well-being and understanding equal opportunity provision aligned with non-discrimination principles A systematic literature review methodology was employed with data extracted and synthesized thematically into key areas like stereotypes well-being impact and equal opportunities Results revealed persistent negative stereotypes contributing to marginalization psychological issues stemming from discrimination with limited mental health support and practical barriers like administrative hurdles and financial constraints impeding educational access The article concludes that providing equal educational opportunities combating discrimination and ensuring access to mental health resources for Venezuelan students is essential to uphold their fundamental human rights and foster an inclusive society that values cultural diversity Therefore supporting their academic success is a vital investment in building a more equitable and culturally rich nation